Prevalence of Methicillin‐Resistant Staphylococcus aureus from Equine Nasopharyngeal and Guttural Pouch Wash Samples. (29th June 2017) - Boyle, A.G.; Rankin, S.C.; Duffee, L.A.; Morris, D.
Abstract : Background: Methicillin‐resistant Staphylococcus aureus (MRSA) is recognized as a cause of nosocomial infections in both human and veterinary medicine. Studies that examine the nasopharynx and guttural pouches of the horse as carriage sites for MRSA have not been reported. Hypothesis/Objective: MRSA colonizes the nasopharynx and guttural pouch of horses. To determine the prevalence of MRSA in equine nasopharyngeal wash (NPW) and guttural pouch lavage (GPL) samples in a field population of horses. Samples: One hundred seventy‐eight samples (123 NPW and 55 GPL) from 108 horses. Methods: Prospective study. Samples were collected from a convenience population of clinically ill horses with suspected Streptococcus equi subsp. equi ( S. equi ) infection, horses convalescing from a known S. equi infection, and asymptomatic horses undergoing S. equi screening. Samples were submitted for S. aureus aerobic bacterial culture with mannitol salt broth and two selective agars (cefoxitin CHROMagar as the PBP2a inducer and mannitol salt agar with oxacillin). Biochemical identification of Staphylococcus species and pulsed‐field gel electrophoresis (PFGE), to determine clonal relationships between isolates, were performed. Results: Methicillin‐resistant Staphylococcus (MRS) was isolated from the nasopharynx of 7/108 (4%) horses. Three horses had MRSA (2.7%), and 4 had MR‐ Staphylococcus pseudintermedius (MRSP). MRSA was isolated from horses on the same farm. PFGE revealed the 3 MRSA as USA 500 strains. Conclusions and Clinical Importance: Sampling the nasopharynx and guttural pouch of community‐based horses revealed a similarly low prevalence rate of MRSA as other studies sampling the nares of community‐based horses. More study is required to determine the need for sampling multiple anatomic sites when screening horses for MRSA.